Solar power optimizer - Ong, Wei Lun. (2011)
This project aims to evaluate and develop of the solar power optimizers under shading conditions. Research and evaluation of SolarMagic power optimizer by National Semiconductor. The evaluation is done indoor using photovoltaic simulator using various panel configuration that includes individual panel, series and parallel connections. All the tests are done with and without the power optimizer. Different sizes of shading are also implemented to observe how the optimizer performs. Impedance matching is used for the design objective of this project. Buck converter is used as an impedance matcher that loads out the maximum power from the solar panel regardless of the load resistance connected. A microchip microcontroller P18F1320 is implemented to generate a PWM signal to drive the MOSFET in the converter. Analog to Digital converter in the microcontroller is used to read the input voltage and current of the solar panel. Various flaws of the buck converter impedance matching are also discussed.